2005
DOI: 10.1007/s00213-005-0220-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of noradrenergic system on the anxiolytic-like effect of DOI (5-HT2A/2C agonists) in the four-plate test

Abstract: These results indicate that the DOI seems to act on the 5-HT2 receptors post-synaptically located. The effect of DOI is regulated by the alpha2-adrenoceptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 59 publications
(63 reference statements)
1
13
0
1
Order By: Relevance
“…The same anxiolytic-like effect following the use of various antidepressants has been proposed [39] . The evidence suggests a strong connection between 5-HT 2A receptors and noradrenaline neurotransmission [39] [40] . It has been demonstrated that another serotonin receptor (5-HT 1A ) not only is involved in the establishment of normal anxiety-like behavior but also that this effect is acting during prenatal and postnatal development [41] [42] .…”
Section: Discussionmentioning
confidence: 95%
“…The same anxiolytic-like effect following the use of various antidepressants has been proposed [39] . The evidence suggests a strong connection between 5-HT 2A receptors and noradrenaline neurotransmission [39] [40] . It has been demonstrated that another serotonin receptor (5-HT 1A ) not only is involved in the establishment of normal anxiety-like behavior but also that this effect is acting during prenatal and postnatal development [41] [42] .…”
Section: Discussionmentioning
confidence: 95%
“…The α 2A AR plays an important role in controlling norepinephrine release and response. This discovery that APP can affect α 2A AR internalization may have an impact on modulation of noradrenergic activity and sympathetic tone, but also affecting pain perception and decreasing epileptogenesis and anxiety ( Hein, 2006 ; Masse et al, 2006 ; Gyires et al, 2009 ; Zhang et al, 2017 ). The noradrenergic system regulates arousal, learning and memory, which has also been implicated in regulating neuroinflammation ( Ardestani et al, 2017 ).…”
Section: β-Arrestin In Agingmentioning
confidence: 99%
“…The a 2A -adrenergic receptor (a 2A AR) is a prototypical GPCR, and mediates a variety of critical physiologic/ pharmacological responses, which include lowering blood pressure, evoking sedation, reducing pain perception, and decreasing epileptogenesis and anxiety (10)(11)(12).…”
mentioning
confidence: 99%